An interdisciplinary review of current and future approaches to improving human–predator relations. Issue 3 (13th February 2017) - Pooley, S.; Barua, M.; Beinart, W.; Dickman, A.; Holmes, G.; Lorimer, J.; Loveridge, A.J.; Macdonald, D.W.; Marvin, G.; Redpath, S.; Sillero‐Zubiri, C.; Zimmermann, A.; et al.
Abstract: In a world of shrinking habitats and increasing competition for natural resources, potentially dangerous predators bring the challenges of coexisting with wildlife sharply into focus. Through interdisciplinary collaboration among authors trained in the humanities, social sciences, and natural sciences, we reviewed current approaches to mitigating adverse human–predator encounters and devised a vision for future approaches to understanding and mitigating such encounters. Limitations to current approaches to mitigation include too much focus on negative impacts; oversimplified equating of levels of damage with levels of conflict; and unsuccessful technical fixes resulting from failure to engage locals, address hidden costs, or understand cultural (nonscientific) explanations of the causality of attacks. An emerging interdisciplinary literature suggests that to better frame and successfully mitigate negative human–predator relations conservation professionals need to consider dispensing with conflict as the dominant framework for thinking about human–predator encounters; work out what conflicts are really about (they may be human–human conflicts); unravel the historical contexts of particular conflicts; and explore different cultural ways of thinking about animals. The idea of cosmopolitan natures may help conservation professionals think more clearly about human–predator relations in both local and global context. These new perspectives for future research practice include a recommendation for focused interdisciplinary research and the use of new approaches, including human‐animal geography, multispecies ethnography, and approaches from the environmental humanities notably environmental history. Managers should think carefully about how they engage with local cultural beliefs about wildlife, work with all parties to agree on what constitutes good evidence, develop processes and methods to mitigate conflicts, and decide how to monitor and evaluate these. Demand for immediate solutions that benefit both conservation and development favors dispute resolution and technical fixes, which obscures important underlying drivers of conflicts. If these drivers are not considered, well‐intentioned efforts focused on human–wildlife conflicts will fail.